MODEL-MODEL KEPEMIMPINAN PENDIDIKAN DALAM PEMBIAYAAN PENDIDIKAN - Elsa Rakhmanita; Nadilatur Rofiqoh; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is a qualitative research employing a literature review approach on models of educational leadership in education financing. The aim of this study is to describe various models of educational leadership in education financing. Data were collected through a literature review from various references. The data analysis technique used is the Miles and Huberman model, which consists of data collection, data reduction, data display, and conclusion drawing. The results of the study indicate that the models of educational leadership in education financing include transformational leadership, transactional leadership, democratic leadership, visionary leadership, and entrepreneurial leadership. Several recommendations for implementing leadership models in education financing include the integration of various leadership models, active stakeholder involvement, the development of alternative funding sources, needs- and priority-based budget planning, enhancement of managerial competencies of educational leaders, and the utilization of technology in financial management. Keywords: Leadership models, education financing